2012
DOI: 10.1038/hr.2011.216
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy for hypertension in the elderly: a sub-analysis of the Combination Therapy of Hypertension to Prevent Cardiovascular Events (COPE) Trial

Abstract: The Combination Therapy of Hypertension to Prevent Cardiovascular Events (COPE) trial demonstrated that the calcium-channel blocker benidipine-based combination therapies with an angiotensin-receptor blocker (ARB), a b-blocker, or a thiazide diuretic (thiazide) were similarly effective in preventing cardiovascular events and achieving the target blood pressure (BP; o140/ 90 mm Hg). We further evaluated the efficacy and safety of these combination therapies in older (X65 years) and younger (o65 years) hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…238 Subgroup analyses from 1 major trial suggest that the benefit of diuretic therapy over ACEI therapy is especially prominent in blacks, 239 and subgroup analysis from another large trial found that β-blockers were significantly less effective than thiazide diuretics and ARBs at preventing stroke in those ≥65 years of age than in younger patients. 240 The results of a recent trial of the direct renin inhibitor aliskiren in patients with type 2 diabetes mellitus plus chronic kidney disease or prevalent CVD did not find evidence that aliskiren reduced cardiovascular end points, including stroke. 241 In general, therefore, although the benefits of lowering BP as a means to prevent stroke are undisputed, there is no definitive evidence that any particular class of antihypertensive agents offers special protection against stroke in all patients.…”
Section: Well-documented and Modifiable Risk Factorsmentioning
confidence: 99%
“…238 Subgroup analyses from 1 major trial suggest that the benefit of diuretic therapy over ACEI therapy is especially prominent in blacks, 239 and subgroup analysis from another large trial found that β-blockers were significantly less effective than thiazide diuretics and ARBs at preventing stroke in those ≥65 years of age than in younger patients. 240 The results of a recent trial of the direct renin inhibitor aliskiren in patients with type 2 diabetes mellitus plus chronic kidney disease or prevalent CVD did not find evidence that aliskiren reduced cardiovascular end points, including stroke. 241 In general, therefore, although the benefits of lowering BP as a means to prevent stroke are undisputed, there is no definitive evidence that any particular class of antihypertensive agents offers special protection against stroke in all patients.…”
Section: Well-documented and Modifiable Risk Factorsmentioning
confidence: 99%
“…The rationale, design, trial management and results of the COPE trial have previously been reported. [16][17][18] In brief, participants with a sitting systolic BP of 140 mm Hg or more and/or a diastolic BP of 90 mm Hg or more, whether untreated or treated, were men and women aged 40 to 85 years who did not achieve the target BP in a sitting position at our clinic following monotherapy with benidipine at a dose of 4 mg day -1 during the run-in phase (4-8 weeks). These patients were randomly assigned to receive benidipine combined with an ARB, a BB or a thiazide.…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
“…The trial results demonstrated that although the percentage of subjects achieving the target BP and the incidence of primary composite cardiovascular end points were similar among the benidipine-thiazide diuretic (TD), benidipine-angiotensin receptor blocker (ARB) and benidipine-b-blocker (BB) groups, second analyses suggested that benidipine combined with a BB appeared to be less beneficial in reducing the risk of stroke compared with the benidipine-thiazide combination, predominantly in the elderly. [16][17][18] Although all benidipine-based regimens were well tolerated, the following adverse events were more frequent than in the other groups: new-onset diabetes and bradycardia in the benidipine-BB group; hyperuricemia, hypokalemia and increased levels of serum creatinine in the benidipine-thiazide group; hyperkalemia in the benidipine-ARB group; vertigo in the benidipine-BB and benidipine-thiazide groups; and increased levels of alanine aminotransferase in the benidipine-ARB and benidipine-thiazide groups. 17 It remains unknown which benidipine-based combination therapy was valuable for preventing the occurrence of specific types of stroke during treatment for hypertension in the COPE trial.…”
Section: Introductionmentioning
confidence: 99%
“…15 Secondary analyses suggested that benidipine combined with a β-blocker was less beneficial in reducing the risk of stroke than the benidipine-thiazide combination. [15][16][17] However, it remains unknown from the COPE trial which benidipine-based combination therapy is most useful for preventing the occurrence of specific types of cardiac events during treatment for hypertension. Thus, in this prespecified subanalysis of the COPE trial, we further evaluated the treatment effects of the 3 benidipine-based regimens in relation to different cardiac events.…”
Section: Demographic and Baseline Patient Characteristics And Bp Contmentioning
confidence: 99%